2014
DOI: 10.1111/clr.12505
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing severity of peri‐implantitis

Abstract: The study indicated that smoking and a prior history of periodontitis were important risk factors for increased severity of peri-implantitis, while concomitant presence of these two risk factors did not further increase the severity of peri-implantitis, as compared to either of these two risk factors alone. Therefore, early diagnosis and adequate treatment of peri-implantitis are important in patients with a prior history of periodontitis and in smokers to minimize the risk of advanced peri-implantitis in conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 17 publications
5
36
0
2
Order By: Relevance
“…This situation has been previously described in the literature, as a clinical study showed that smokers had a two‐fold higher chance for the development of peri‐implant pathologies than non‐smokers 42 . This trend is in agreement with the findings of Saaby et al, 43 who reported smoking as the most important risk factor for increased severity of peri‐implantitis.…”
Section: Discussionsupporting
confidence: 91%
“…This situation has been previously described in the literature, as a clinical study showed that smokers had a two‐fold higher chance for the development of peri‐implant pathologies than non‐smokers 42 . This trend is in agreement with the findings of Saaby et al, 43 who reported smoking as the most important risk factor for increased severity of peri‐implantitis.…”
Section: Discussionsupporting
confidence: 91%
“…This is probably related to the association of a lack of adequate KT around endosseous dental implants with more plaque accumulation, tissue inflammation, mucosal recession, and attachment loss. Conversely, similar studies were not able to find a clear association between the absence of keratinized peri-implant mucosa and peri-implant disease [7826]. The results obtained in the present study corroborated those reported in a recent systematic review, emphasizing the importance of an adequate zone of KT surrounding implants so that better peri-implant tissue health may be achieved [27].…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to orthopedic implants that are placed sub-merged into sterile tissue, dental implants are placed trans-mucosally in the jaw bone with their upper portion exposed to the oral cavity during healing because they are positioned to support prosthetic teeth. To date polymicrobial infections such as peri-implantitis remain an important cause for implant failure, especially in patients with a previous history of periodontal diseases [5, 46]. To address the potential of our 12 min UV-treatment to improve this critical aspect of implant failure, we investigated if the changes in titanium surface properties had an effect on the attachment and biofilm formation of human oral bacteria.…”
Section: Discussionmentioning
confidence: 99%